The differences of blood type in relation to psoriasis and its onset: Cross sectional study - Dharmawan, Nugrohoaji; Widhiati, Suci; Oktavriana, Triasari; Harahap, Irene Jessica Pinarsinta (UI Scholars Hub, 2021)
Background: Psoriasis is a chronic skin disease caused by inflammatory response and attacks 2% of population, with the prevalence influenced by age, geographical location, and genetic background. Until this day, there are several studies that discuss about the relationship between blood type with disease. However, discussion about the difference between blood type and the relationship with skin disease remains limited. The objective of this study is to know the relationship between blood type, psoriasis, and onset of psoriasis.Methods: This study adopted cross-sectional design of analytic observational study. The subjects of this study were patients in Department of Dermatology and Venereology at Dr. Moewardi General Hospital and UNS Hopital in Surakarta. The blood types were determined by two methods; by using ABD-Pad measurement tools that able to see the reaction of antigen and antibody in short time and by using the hospital’s laboratory facility where sample was taken. Anamnesis were done to collect data about the onset of psoriasis. Chi-square (X2) statistical test was used to analyze the data.Results: Total sample of this study were 62 people with 31 subjects (50%) were psoriasis patients and 31 others (50%) are non-psoriasis patients. Chi-square test (X2) between blood type with psoriasis and blood type with the onset of psoriasis are p = 0.269 and p = 0.188 respectively. Conclusion: The significance level used was p < 0.05, therefore there’s no significant correlation between blood type with psoriasis and the onset of psoriasis.